PENGARUH MOTIVASI INTRINSIK TERHADAP PERFORMA ATLET TAEKWONDO PADA SAAT LATIHAN REVIEW LITERATUERE - Michael Johannes Hadiwijaya Louk; Al Ihzan Tajuddin; Eduardus Mario De Yesus (Nusa Cendana University, 2021)
Taekwondo is a type of martial arts sport that is often competed at national or international events. The purpose of this study was